Anthropological approaches for cultural resource conservation design and planning. (2nd October 2019) - Brown, Madeline; Murtha, Timothy
ABSTRACT: How natural and cultural resources are defined and valued has implications for their conservation and assessment. Although legal regulations for cultural resources such as the National Historic Preservation Act or the Native American Graves Protection and Repatriation Act offer clear guidelines for evaluating entities that fall under their jurisdiction, cultural resources cover far more than these official definitions encompass. Cultural models of cultural resources may vary across individuals from different management agencies, geographic regions, or cultural backgrounds. This in turn affects how they value and perceive cultural resources, both in their work and daily life. Anthropological methods including ethnography, cultural domain analysis, participatory action research, and crowdsourcing can offer critical insights into how different stakeholders or actors classify and perceive cultural resources. By recognizing the variability and dynamism in cultural resource definitions and values, it is possible to develop more holistic and inclusive assessment criteria for management and conservation. Developing emic understandings of cultural resources is particularly important in contexts with diverse populations, nested management institutions, and competing land-use priorities. This paper highlights methodologies for incorporating anthropological methods into integrated landscape conservation design and offers recommendations for how these methods can be applied.